2019
DOI: 10.1002/2211-5463.12632
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cellular responses to replication stress leading to apoptosis or senescence

Abstract: Replication stress ( RS ) is a major driver of genomic instability and tumorigenesis. Here, we investigated whether RS induced by the nucleotide analog fludarabine and specific kinase inhibitors [e.g. targeting checkpoint kinase 1 (Chk1) or ataxia telangiectasia and Rad3‐related ( ATR )] led to apoptosis or senescence in four cancer cell lines differing in TP 53 mutation status and expression of lamin A/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…But there were similar differences between the subclones in other oncogenic pathways as well. For instance, replication stress is a major contributor to apoptosis (Hills and Diffley, 2014;Lukášová et al, 2019), and we found consistent differences in apoptotic pathway scores between the subclones in the tumors ( Supplementary Table 15) -which is also concordant with observations made using multi-region bulk sequencing data (Figure 2D and Supplementary Figure 31) and TCGA data (Supplementary Figure 15). Nonetheless, some other cancer-related pathway activities also showed significant intra-tumor regional differences, even within the same subclones (Figure 5F and Supplementary Figure 32).…”
Section: Heterogeneity Analysis At Single Cell Resolutionsupporting
confidence: 89%
“…But there were similar differences between the subclones in other oncogenic pathways as well. For instance, replication stress is a major contributor to apoptosis (Hills and Diffley, 2014;Lukášová et al, 2019), and we found consistent differences in apoptotic pathway scores between the subclones in the tumors ( Supplementary Table 15) -which is also concordant with observations made using multi-region bulk sequencing data (Figure 2D and Supplementary Figure 31) and TCGA data (Supplementary Figure 15). Nonetheless, some other cancer-related pathway activities also showed significant intra-tumor regional differences, even within the same subclones (Figure 5F and Supplementary Figure 32).…”
Section: Heterogeneity Analysis At Single Cell Resolutionsupporting
confidence: 89%
“…Notably, BdS or ATL in combination with olaparib resulted in highly synergistic increases in bulky chromatin bridge formation (Figure 5A). Additional bridges were identified following RPA1 staining, representing the induction of two key anaphase bridge subtypes by the combination treatments: bulky, DAPI-positive chromatin bridges and ultra-fine, DAPI-negative but RPA1-positive (RPA1+) bridges (Figure 5B; both subtypes represented) [49,50]. In line with mitotic dysregulation, we also detected a synergistic increase in the percentage of micronuclei present upon combination treatment of BdS or ATL with olaparib (Figure 5C).…”
Section: Combination Treatment Of Bds or Atl With Olaparib Induces Pleiotropic Mitotic Defectssupporting
confidence: 60%
“…As a result, the micronuclei consisted of both the γH2AX(+) subtype, arising from DSB clusters occurring in S phase and the γH2AX(−) subtype, typically resulting from lagging chromosomes [51,52]. The chromatin bridging we observed characteristically occurs at replication intermediates, such as stalled replication forks or under-replicated regions (e.g., common fragile sites) that enter mitosis despite their intermediate state, or dicentric chromosomes more generally [5,7,49,50,62]. Such events have been observed following transient G2 delays due to mild replication stress, which is consistent with the sequence of events we observed [54].…”
Section: Discussionmentioning
confidence: 83%
“…The changes occurred in a high proportion of cells of different histological origin. We also showed that the LBR/LB1 reduction induced by cell irradiation appears as a characteristic marker of cells determined to be headed to senescence after exposure to genotoxic stress [23,24].…”
Section: Discussionmentioning
confidence: 59%
“…Thus, LINC complex mutations are likely to have an effect on NE integrity, resulting in the uncoupling of the nucleoskeleton and cytoskeleton [20][21][22]. We recently found that DNA damage induced by γ-irradiation or replication stress (RS) in cancer cells leads to downregulation of the lamin B receptor (LBR) and lamin B1 (LB1) associated with changes in nuclear morphology [23,24]. LBR is an integral protein of the inner nuclear membrane (INM) which preferentially binds to LB1 at the N terminal [25].…”
mentioning
confidence: 99%